2022
DOI: 10.1038/s41419-021-04478-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents methylglyoxal-induced apoptosis by suppressing oxidative stress in vitro and in vivo

Abstract: Methylglyoxal (MGO) is an active metabolite of glucose and plays a prominent role in the pathogenesis of diabetic vascular complications, including endothelial cell apoptosis induced by oxidative stress. Metformin (MET), a widely prescribed antidiabetic agent, appears to reduce excessive reactive oxygen species (ROS) generation and limit cell apoptosis. However, the molecular mechanisms underlying this process are still not fully elucidated. We reported here that MET prevents MGO-induced apoptosis by suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 63 publications
(66 reference statements)
3
37
0
Order By: Relevance
“…Moreover, the data presented in this review indicate that in order to suppress atherogenesis and endothelial dysfunction it is necessary to inhibit not only (and perhaps not so much) the accumulation of primary products (LOOH) in LDL, but also the accumulation of secondary products of free radical oxidation—low molecular weight dicarbonyls. Positive examples of influencing the intensity of free radical oxidation using biguanides—dicarbonyl scavengers [ 101 , 113 , 114 , 115 ] and aldehyde-binding imidazole-containing peptides [ 116 , 117 ] already exist. In particular, the use of biguanides significantly suppressed the manifestation of oxidative and carbonyl stress in diabetic patients without the administration of any antioxidants (the so-called “quasi-antioxidant effect”) [ 101 ].…”
Section: Antioxidants In Cardiology: Pro Et Contramentioning
confidence: 99%
“…Moreover, the data presented in this review indicate that in order to suppress atherogenesis and endothelial dysfunction it is necessary to inhibit not only (and perhaps not so much) the accumulation of primary products (LOOH) in LDL, but also the accumulation of secondary products of free radical oxidation—low molecular weight dicarbonyls. Positive examples of influencing the intensity of free radical oxidation using biguanides—dicarbonyl scavengers [ 101 , 113 , 114 , 115 ] and aldehyde-binding imidazole-containing peptides [ 116 , 117 ] already exist. In particular, the use of biguanides significantly suppressed the manifestation of oxidative and carbonyl stress in diabetic patients without the administration of any antioxidants (the so-called “quasi-antioxidant effect”) [ 101 ].…”
Section: Antioxidants In Cardiology: Pro Et Contramentioning
confidence: 99%
“…Intrathecal injection of metformin also significantly reduced the upregulated MGO in the dorsal horn and mechanical pain induced by bortezomib treatment, which may be related to RAGE/STAT3 signalling pathway 68 . Metformin also reduced MGO‐induced apoptosis by inhibiting oxidative stress in vivo and in vitro 69 . Taken together, the data suggested that metformin, as an MGO scavenger, may serve as a disease reliever in PDPN.…”
Section: Effects and Mechanisms Of Metformin On Pdpnmentioning
confidence: 73%
“… 68 Metformin also reduced MGO‐induced apoptosis by inhibiting oxidative stress in vivo and in vitro. 69 Taken together, the data suggested that metformin, as an MGO scavenger, may serve as a disease reliever in PDPN.…”
Section: Effects and Mechanisms Of Metformin On Pdpnmentioning
confidence: 85%
“…In addition, it was found that the production of MDA increased and the activity of GSH-Px decreased in HG-induced HUVEC cells, vaccarin treatment could reverse these phenomena ( Figures 4F, G ), indicating that vaccarin could also play an anti-inflammatory role in vitro . Metformin (MET) had been widely proven to relieve inflammatory injury in T2DM( Karam and Radwan 2019 ; Raj, Natarajan et al, 2021 ; Wang, Wang et al, 2022 ). Therefore, we used metformin as a positive control to compare the effects of vaccarin and found that the effect of vaccarin on the inflammatory injury was similar to that of metformin ( Figures 4A–G ).…”
Section: Resultsmentioning
confidence: 99%